2023
DOI: 10.3390/ijms241612639
|View full text |Cite
|
Sign up to set email alerts
|

Antiseizure Medications in Alzheimer’s Disease from Preclinical to Clinical Evidence

Abstract: Alzheimer’s disease (AD) and epilepsy are common neurological disorders in the elderly. A bi-directional link between these neurological diseases has been reported, with patients with either condition carrying almost a two-fold risk of contracting the other compared to healthy subjects. AD/epilepsy adversely affects patients’ quality of life and represents a severe public health problem. Thus, identifying the relationship between epilepsy and AD represents an ongoing challenge and continuing need. Seizures in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 112 publications
0
0
0
Order By: Relevance
“…Interestingly, preclinical studies have shown that some antiseizure medications (ASMs) targeting abnormal network hyperexcitability might change the natural progression of AD [33], though this needs to be demonstrated. The study by Bosco et al [34] highlighted the need for future studies to be directed toward detecting AD patients with subclinical epileptiform activity and to definitely establish the usefulness of ASMs in ADRD.…”
mentioning
confidence: 99%
“…Interestingly, preclinical studies have shown that some antiseizure medications (ASMs) targeting abnormal network hyperexcitability might change the natural progression of AD [33], though this needs to be demonstrated. The study by Bosco et al [34] highlighted the need for future studies to be directed toward detecting AD patients with subclinical epileptiform activity and to definitely establish the usefulness of ASMs in ADRD.…”
mentioning
confidence: 99%